[Rezension von: In and Out of This World: Material and Extraterrestrial Bodies in the Nation of Islam By S. C. Finley (2022)] - Andersen, Nick (Body and religion, 2022)
In and Out of This World: Material and Extraterrestrial Bodies in the Nation of Islam By S. C. Finley (2022) Durham: Duke University Press, xi + 252pp., 4 figures